Evaluation of Holsten Crossbred Bulls based on milk composition of progeny - Radhika G (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 1998)
Sire evaluation programmes in Kerala state, so far have been hinged around milk production alone, and no emphasis has been laid on milk constituents. The milk constituents like fat and solids not fat determined the market value and consumer's receptivity of milk. Reports on sire evaluation on the basis of milk constituents were seriously lacking in literature and hence the present investigation was undertaken with a view to compare the crossbred sires on the basis of milk yield, fat, total solids, and solids not fat percentages and their yields. 1284 milk samples belonging to 222 animals (103 progenies of Holstein crossbred bulls with superior genetic worth and 119 contemporaries) calved during the period 1995~96 formed the material for the study. These animals belonged to farmers in the area of six AI centres around Thrissur and also the animals maintained in three University Livestock farms. Milk samples were collected during early, middle and late lactation both in morning and evening, and the samples were analysed for fat, total solids and solids not fat percentages. Milk fat percentage was estimated by Electronic Milk Tester with frequent standardisation with Gerber's method. Total solids percentage was determined by Gravimetric method and solids not fat by finding the difference between total solids and fat percentages of milk. Fat, total solids and solids not fat yields were calculated by multiplying the percentages of these constituents with cumulative milk yield for each stage for lactation and adding.